2023
DOI: 10.1186/s13005-023-00347-4
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional condylar positional and morphological changes following mandibular reconstruction based on CBCT analysis: a prospective study

Abstract: Objective This study aimed to evaluate the condylar positional changes following mandibular reconstruction with preservation of the condylar head using Cone-Beam Computed Tomography (CBCT). Also, to assess joint space changes and the overall volumetric space compared to the preoperative status. Methodology This prospective study included 30 patients (60 joints) subjected to unilateral mandibular resection and reconstruction with preservation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Wei et al analyzed the CT images of 16 patients’ TMJs pre- and postoperatively and found that the ipsilateral condyles moved anteroinferiorly immediately after surgery and then moved anterosuperiorly thereafter [ 12 ]. Saddam et al examined the CBCT scans of 30 patients who underwent unilateral mandibular reconstruction to study their condylar positions and found that condylar position changed in a downward direction and became larger as time went on, whereas there were no significant differences in the anteroposterior direction [ 13 ]. In this study, the condylar position changed in the patients in both the 3D group and the traditional group after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al analyzed the CT images of 16 patients’ TMJs pre- and postoperatively and found that the ipsilateral condyles moved anteroinferiorly immediately after surgery and then moved anterosuperiorly thereafter [ 12 ]. Saddam et al examined the CBCT scans of 30 patients who underwent unilateral mandibular reconstruction to study their condylar positions and found that condylar position changed in a downward direction and became larger as time went on, whereas there were no significant differences in the anteroposterior direction [ 13 ]. In this study, the condylar position changed in the patients in both the 3D group and the traditional group after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We also assessed the relationship between occlusal changes and mandibular condyle position using categorical variables (Table 3). The APP criteria used in this study were primarily used to assess the position of the mandibular condyle in relation to the skeleton [17] or changes in the position of the mandibular condyle after bimaxillary surgery [18,24]. Although condylar position may not be a determinant of TMJ pathophysiology [24,25], frequency analysis of condylar position over time may provide helpful information for clinicians diagnosing and treating TMJ OA.…”
Section: Discussionmentioning
confidence: 99%
“…Among the JS measurements, AJS and PJS were used to calculate information about the anteroposterior position (APP) of the mandibular condyle in the glenoid fossa. The APP is defined as the position obtained by dividing AJS by PJS (AJS/PJS ratio) and is considered a central condylar position when the calculated value is 1 (±0.09), a posterior condylar position when it is greater than 1, and an anterior condylar position when it is less than 1 [17,18].…”
Section: Data Analysis Of Cbct Imagesmentioning
confidence: 99%
“…The sample size was calculated using the G* Power software (version 3.1; Universität Kiel). Considering α = 0.05, β = 0.2, t-test for matched pairs, and an effect size of 0.8 [20,21], the sample size was calculated as at least 15 patients per group.…”
Section: Sample Size Calculationmentioning
confidence: 99%